Las imágenes fotográficas de la sociedad mexicana en la prensa gráfica del porfiriato - Torre Rendón, Judith de la (El Colegio de México, A.C., 1998)
This text analyzes the photographic images of the Porfirian elite that appeared in the 1891-1910 graphic press, seeking to demonstrate how the illustrated magazines of that time both projected an image of order and progress, and divulged the well being and relaxation of the more privileged social groups. It also outlines a close relation between these photographic themes and the progress and concepts particular of both photography and press reports.